The colliding of high Mach number plasma jets: a kinetic investigation - W.-B. Zhang; Y.-H. Li; D. Wu; J. Zhang (Nuclear Fusion)
Colliding of two high Mach-number plasma jets is one of the methods for generating shocks, offering valuable insights for inertial confinement fusion (ICF) and astrophysics. Especially, quantum degeneracy and kinetic effects appear when the colliding plasma jets are of high density and high Mach number, which play critical roles in the resulting dynamics. Recently, the double-cone ignition (DCI) project provides an unprecedented experimental platform for investigating the collision of plasma to explore many new physical phenomena. In this work, a theoretical analysis was conducted using the newly developed hybrid particle-in-cell (PIC) LAPINS code, covering a vast range of plasma densities and temperatures. The results reveal that electron degenerate pressure in the upstream region suppresses the growth of the downstream density. Moreover, under extremely high Mach number collisions of moderately dense plasma, a significant non-equilibrium kinetic effect, namely cross penetration, is observed, along with an anomalous decrease in the downstream density compression ratio, contrary to expectations of monotonic growth. These findings provide valuable suggestions for the baseline design of the DCI scheme and related ICF shock studies, and offer potential analogies to astrophysical processes such as white dwarf mergers and shocks in dense nebulae.